Variability of Human Systemic Humoral Immune Responses to Adenovirus Gene Transfer Vectors Administered to Different Organs - Harvey, Ben-Gary (American Society for Microbiology, 1999)
Administration of adenovirus (Ad) vectors to immunologically naive experimental animals almost invariably results in the induction of systemic anti-Ad neutralizing antibodies. To determine if the human systemic humoral host responses to Ad vectors follow a similar pattern, we evaluated the systemic (serum) anti-Ad serotype 5 (Ad5) neutralizing antibodies in humans after administration of first generation (E1(−) E3(−)) Ad5-based gene transfer vectors to different hosts. Ad(GV)CFTR.10 (carrying the normal human cystic fibrosis [CF] transmembrane regulator cDNA) was sprayed (8 × 10(7) to 2 × 10(10) particle units [PU]) repetitively (every 3 months or every 2 weeks) to the airway epithelium of 15 individuals with CF. Ad(GV)CD.10 (carrying the Escherichia coli cytosine deaminase gene) was administered (8 × 10(8) to 8 × 10(9) PU; once a week, twice) directly to liver metastasis of five individuals with colon cancer and by the intradermal route (8 × 10(7) to 8 × 10(9) PU, single administration) to six healthy individuals. Ad(GV)VEGF121.10 (carrying the human vascular endothelial growth factor 121 cDNA) was administered (4 × 10(8) to 4 × 10(9.5) PU, single administration) directly to the myocardium of 11 individuals with ischemic heart disease. Ad vector administration to the airways of individuals with CF evoked no or minimal serum neutralizing antibodies, even with repetitive administration. In contrast, intratumor administration of an Ad vector to individuals with metastatic colon cancer resulted in a robust antibody response, with anti-Ad neutralizing antibody titers of 10(2) to >10(4). Healthy individuals responded to single intradermal Ad vector variably, from induction of no neutralizing anti-Ad antibodies to titers of 5 × 10(3). Likewise, individuals with ischemic heart disease had a variable response to single intramyocardial vector administration, ranging from minimal neutralizing antibody levels to titers of 10(4). Evaluation of the data from all trials showed no correlation between the peak serum neutralizing anti-Ad response and the dose of Ad vector administered (P > 0.1, all comparisons). In contrast, there was a striking correlation between the peak anti-Ad5 neutralizing antibody levels evoked by vector administration and the level of preexisting anti-Ad5 antibodies (P = 0.0001). Thus, unlike the case for experimental animals, administration of Ad vectors to humans does not invariably evoke a systemic anti-Ad neutralizing antibody response. In humans, the extent of the response is dictated by preexisting antibody titers and modified by route of administration but is not dose dependent. Since the extent of anti-Ad neutralizing antibodies will likely modify the efficacy of administration of Ad vectors, these observations are of fundamental importance in designing human gene therapy trials and in interpreting the efficacy of Ad vector-mediated gene transfer.